EXPLORATION OF AI TOOLS THROUGH THE LENS OF UNIVERSAL DESIGN FOR LEARNING - Choi, Cynthia (PUPIL: International Journal of Teaching, Education and Learning, 2024)
This presentation explores the interplay between Universal Design for Learning (UDL) principles and accessible technology, with a particular focus on AI-powered tools. UDL is a pedagogical framework centered on providing diverse learners with multiple means of engagement, representation, and action/expression. These principles lay a foundation to redevelop curriculum and teaching strategies that address all learners’ needs and offer meaningful integration of technology opportunities in supporting the key facets of UDL. In response to the transformative potential of generative AI tools, this exploration examines a diverse array of AI-powered applications through the lens of UDL. Valuable insights gleaned from inservice teachers participating in a technology-integration course will be shared, offering practical perspectives on how AI applications may be harnessed to support UDL in real-world classroom settings.